The Influence of The Jigsaw Model on The Learning Outcomes of Class V Tema 1 Subtema 1 SD 091254 Batu Onom T.A 2023/2024 - Devi Sri Ayuni; Yanti Arasi Sidabutar; Lisbet Novianti Sihombing (MultiTech Publisher, 2023)
The aim of this research is to find out whether the Jigsaw model has an effect on the learning outcomes of class V students in theme 1 subtheme 1 at SD Negeri 091254 Batu Onom. There are 2 hypotheses in this research, namely (1) there is an influence on the learning outcomes of class V students in theme 1 Subtheme 1 at SD Negeri 091254 Batu Onom (Ha) and (2) there is no influence of the jigsaw model on the learning outcomes of class V students in theme 1 subtheme 1 at State Elementary School 091254 Batu Onom(Ho). This research method is an experimental method with a Pre-Experiment Design type of research according to the number of samples to be studied. The research design used was a one-group pretest-posttest design which only involved one class, namely the experimental class without a comparison class. The population of this study was 30 grade IV students at State Elementary School 091254 Batu Onom. Data collection was carried out using text techniques, observation, documentation. Then, the total pretest score in the experimental class was obtained, namely with an average score of 48.16 and posttest 89.5. So it can be concluded that there is an influence of the Jigsaw model on the learning outcomes of class V students in theme 1 subtheme 1 at SD Negeri 091254 Batu Onom. This H a is accepted and H 0 is rejected.